INDUSTRI HIBURAN DALAM ISLAM: ANALISIS DARI SUDUT PERSEJARAHAN AWAL DAN PENILAIAN HUKUM - Yusof, Abdullah (Jurnal Syariah, 2019)
This article in its first part surveys the existence of entertainments, i.e music, instruments, song and others in the early period of Islam especially during the reign of Umawiyyah and 'Abbasiyyah. It elaborates the involvement of some caliphs in supporting the activities of enjoyment and entertainment. As it is understood, music itself is allowed, however due to some occassions and situations, it might be prohibited (unlawful). The author analyses Muslim scholars' view on entertainment, music, song and Singing as a part of human "enjoying ".